If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + PX = 5 Reorder the terms: PX + 9x = 5 Solving PX + 9x = 5 Solving for variable 'P'. Move all terms containing P to the left, all other terms to the right. Add '-9x' to each side of the equation. PX + 9x + -9x = 5 + -9x Combine like terms: 9x + -9x = 0 PX + 0 = 5 + -9x PX = 5 + -9x Divide each side by 'X'. P = 5X-1 + -9xX-1 Simplifying P = 5X-1 + -9xX-1
| 6y=x+42 | | ?7+2?10+?7-2?10=2?5 | | 8(2s+3)=-4(5s+4) | | 8+5x=-17 | | 5x-20=-40 | | 10x^3-4x^2= | | A=a+(n-4)forn | | -7x-24=32 | | A=a+(n-4) | | 8xy-6=114 | | 5x+8+x-10=22 | | 6x-18=22 | | 2(3.14)(4)= | | 2c-5(5c-6)+6(2c-6)+3c+3= | | c=8-(-9) | | 4s+6=14 | | 3x+2+7=8x-1 | | A=-9(-4) | | 14-3t=50 | | 24=36 | | 9x-4=3(3x+1) | | 0.3x+0.2y=0.3 | | 8x+12y=21 | | (3x)=(4x-15) | | 12=6x-13-x | | 1.18+4.43x-4.9x^2=0 | | 4x^2+25x=56 | | Y=2.76+0x | | 1.18+4.43x-4.9t^2=0 | | 5(2x-9)=26 | | 9.8x^2-10x-60=0 | | -10c^2d=15cd^2 |